Altercentric intrusions from multiple perspectives: beyond dyads. - Francesca Capozzi; Andrea Cavallo; Tiziano Furlanetto; Cristina Becchio (PLoS ONE)
Recent findings suggest that in dyadic contexts observers rapidly and involuntarily process the visual perspective of others and cannot easily resist interference from their viewpoint. To investigate whether spontaneous perspective taking extends beyond dyads, we employed a novel visual perspective task that required participants to select between multiple competing perspectives. Participants were asked to judge their own perspective or the visual perspective of one or two avatars who either looked at the same objects or looked at different objects. Results indicate that when a single avatar was present in the room, participants processed the irrelevant perspective even when it interfered with participants' explicit judgments about the relevant perspective. A similar interference effect was observed when two avatars looked at the same discs, but not when they looked at different discs. Indeed, when the two avatars looked at different discs, the interference from the irrelevant perspective was significantly reduced. This is the first evidence that the number and orientation of agents modulate spontaneous perspective taking in non-dyadic contexts: observers may efficiently compute another's perspective, but in presence of more individuals holding discrepant perspectives, they may not spontaneously track multiple viewpoints. These findings are discussed in relation to the hypothesis that perspective calculation occurs in an effortless and automatic manner.